INFLUENCE OF THICKNESS AND GRANULOMETRIC COMPOSITION OF GRANULAR ASPHALT ON ITS STRENGTH CHARACTERISTICS WHEN PLACING INTO THE ROAD PAVEMENT - Pahomova, Ekatarina Gennadievna; Andrianov, Konstantin; Zubkov, Anatoly; Monastyrev, Pavel (Journal of Applied Engineering Science, 2020)
When performing roadway replacement and reconstruction works, the removal of the road surface by self-propelled road milling machineis provided. The material obtainedduring milling (granular asphalt) is used in the base layers and lower layers of the coating, provided that the strength requirements are met. The effectiveness of the applied technology in the construction of structural layers of road pavement depends on considering the properties of the used material and the parameters of the mechanic means during works. We have reviewed the influence of the granulometric composition and   the granular asphalt layer thickness on its strength properties in the construction of road structures. On the basis of experimental studies, analytical dependences are obtained for calculating the deformation and compacting factor under the action of the compaction loading of used granular asphalt. We have obtained the results tocalculate the deformation-stress relationship and the dependence of the compacting factor on deformation, taking into account the granulometric composition and layer thickness. That allowsto justify the parameters of compacting machines to ensure the required quality of compacting of the granular asphalt layer.
Keywords: granular asphalt, compacting, stress, deformation